Dos notas de sinonimia sobre Hemiptera neotropicales (Hemiptera: Heteroptera). - Pirán, Augusto A. (Beiträge zur Entomologie = Contributions to Entomology, 1955)
Nomenklatorische Handlungen bolivianus Kormilev, 1951 (Daimonocoris), syn. n. of Brachystethus vexillum Breddin, 1903 peruviana Jensen-Haarup, 1931 (Murgantia), syn. n. of Murgantia simulans Distant, 1911